Transcriptomics data of a human in vitro model of non-alcoholic steatohepatitis exposed to elafibranor - Joost Boeckmans; Karolien Buyl; Alessandra Natale; Valerie Vandenbempt; Steven Branson; Veerle De Boe; Vera Rogiers; Joery De Kock; Robim M. Rodrigues; Tamara Vanhaecke (Data in Brief, 2019)
The present dataset contains the transcriptomic characterization of a novel in vitro model of non-alcoholic steatohepatitis (NASH) as well as its transcriptomics read-outs for the evaluation of elafibranor, a potential anti-NASH compound. We report whole genome microarray data (Affymetrix HG U133 plus 2.0) of human multipotent stem cell-derived hepatic cells (hSKP-HPC) exposed to mediators of NASH. These cells were exposed to lipogenic inducers (insulin, glucose, fatty acids) and pro-inflammatory factors (IL-1β, TNF-α, TGF-β) to trigger hepatocellular responses characteristic of NASH. In addition, to evaluate the anti-NASH features of elafibranor, a dual peroxisome proliferator-activated receptor (PPAR) agonist that currently is under investigation as a potential anti-NASH therapeutic, was tested this in vitro set-up.This paper provides a detailed description of the microarray data as well as an indication of their value for evaluating cell signaling pathways (e.g. NFκB network) during the in vitro evaluation of anti-NASH compounds. Raw microarray data of different testing conditions were deposited as.CEL files in the Gene Expression Omnibus of NCBI with GEO Series accession number GSE126484. Further interpretation and discussion of these data can be found in the corresponding research article (DOI: 10.1016/j.phrs.2019.04.016) Boeckmans et al., 2019. Keywords: NASH, Elafibranor, In vitro, Transcriptomics